Bartonella in bat flies from the Egyptian fruit bat in the Middle East - Špitalská, Eva; Ševčík, Martin; Peresh, Yevheniy-Yuliy; Benda, Petr (Parasitology research, 2024)
In the family of fruit bats, Pteropodidae Gray, 1821, as in the third most diverse group of bats (Chiroptera), the bacterium of the genus Bartonella was detected in several species as well as in a few species of their insect ectoparasites in some tropical and sub-tropical regions of the Old World. The Egyptian fruit bat, Rousettus aegyptiacus (Geoffroy, 1810), is one of the most widespread fruit bats, occurring between South Africa, Senegal, and Pakistan. In this bat species, Candidatus Bartonella rousetti has been detected in three African populations in Nigeria, Kenya, and Zambia. This fruit bat, however, also occurs in the Palaearctic, an area isolating the species geographically and phylogenetically from the Afrotropical part of its distribution range. We screened the blood-sucking bat flies (family Nycteribiidae) from R. aegyptiacus for the presence of the Bartonella bacteria. A rich material of bat fly Eucampsipoda aegyptia (Macquart, 1850), a monoxenous ectoparasite of the Egyptian fruit bats, was collected at 26 localities in seven countries (Egypt, Iran, Jordan, Lebanon, Oman, United Arab Emirates, and Yemen) of the Middle East in 2007-2013. The DNA isolates from the bat flies were subjected to a three-marker (gltA, ssrA, and intergenic spacer region, ITS) multilocus sequence analysis. Based on the amplification of the fragment of ssrA gene by a real-time PCR, 65 E. aegyptia samples from 19 localities in all seven countries were positive for the bacteria. One to five Bartonella-positive individuals of E. aegyptia were collected per one individual of R. aegyptiacus. An analysis of the ITS and gltA genes indicated the presence of an uncultured Bartonella sp., belonging to the Cand. B. rousetti genogroup, identified from populations of the Egyptian fruit bat in Africa. These results support the hypothesis that Bartonella's diversity corresponds to its host's diversity (and phylogenetic structure). Specific lineages of pathogens are present in specific phylogenetic groups of bats.
Keywords: intergenová DNA; Phylogeny; Kenya; Humans; zvířata; Chiroptera; Middle East; fylogeneze; Keňa; Animals; DNA, Intergenic; Bartonella; lidé; Střední východ